Regulasi Tentang Pornografi: Tinjauan Kontekstual Hukum Islam - Hamdan Hamdan (Ulumuna, 2006)
The issue and reality of pornography is as old as the civilization of human beings. The sensitivity of pornography-porno actions in the context of Indonesian society with the biggest number of muslims population in the world is getting hotter along with the plan to regulate the pornography. Pro-cont of pornography is related to definition, criteria and limitation of pornography- porno actions. The polemic becomes more complicated when it is associated with economy, politics, religion, art, etc. Although it is not a major issue anymore—as it was few months ago—this writing aims at giving reflection on pornography dealing with Islamic law mainly on the aspect of law concluding (istinbat al-hukm) and aspect of profit and loss. The reflection of Islamic law on genitals and the reposition of knowledge of Islamic law as individual and social ethic controlled by society and State will be analyzed deeper in this writing.